A GIS-based Flood Risk Assessment in the Urban Catchment of Uyo Metropolis, Nigeria - Dickson Kinikawo Nsiegbe; Vincent E Weli; Gift O Chukwu-Okeah; Olatunde S Eludovin; Temple Probyne Abali; Inko-Tariah Ibiso Michael; Lucky Baripara Nkii (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Flood occurs as a result of rising global temperatures, more precipitation, increased runoff, and an increase in the rate of urban flooding. The goal of this research is to calculate the flood risk assessment of a selected urban catchment in the Nigerian metropolis of Uyo. Secondary data were obtained from Landsat images of the study area using a correlational research design. Using supervised categorization of landuse in the area, the watershed pattern, landuse/landcover, and inundation level were determined using the area's Digital Elevation Model. The study also used a GIS-assisted computer simulation of storm water created by enhanced DEM to assess storm water level and inundation as a function of landuse/landcover change. Storm water generation assessment, inundation modeling, assessment of land cover and level of inundation, and evaluation of flash flood susceptibility using modeled inundation were among the hydrological models and techniques used to analyze the data. The findings revealed that Uyo has a number of streams with varying flow lengths. Uyo has 21 sub-basins, according to the study. In uyo, the total runoff was greater (0.74) inches. In Uyo, the rate of change in catchment behavior, such as catchment precipitation, node flooding, and runoff, increased with the time of day, whereas the rate of change in runoff volume varied somewhat. The hydrograph was not wider because the sections of Uyo metropolitan that were prone to moderate and high floods were higher (78.03 percent ). Based on these findings, the study suggests that better city design is needed to control the impact of flooding in the study area. To prevent the loss of life and property, areas prone to moderate and high flood vulnerability should be closely monitored and secured.